Pengaruh Harga, Cita Rasa, dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Ayam Geprek Arya - Iqbal Ade Saputra; Ferdika Setiadi Kurniawan; Zaenal Abidin; Ahmad Ubaidilah Yahya; Fikri Riski Utama (Indo Publishing, 2025)
This study aims to analyze the influence of price, taste, and service quality on consumer satisfaction at Ayam Geprek Arya, a popular culinary choice among students of UIN Jurai Siwo Lampung. A quantitative approach with an associative research design was employed. The sample consisted of 100 respondents selected using purposive sampling, specifically students who had purchased Ayam Geprek Arya. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The results show that price, taste, and service quality have a positive and significant effect on consumer satisfaction, both partially and simultaneously. Taste emerged as the most dominant factor influencing consumer satisfaction. The coefficient of determination (R²) of 0.746 indicates that the three variables collectively explain 74.6% of the variations in consumer satisfaction. These findings confirm that a combination of appropriate pricing, consistent taste quality, and good service plays a crucial role in creating consumer satisfaction in the culinary business of Ayam Geprek Arya.